Performance Evaluation of OMDV and DSDV Routing Protocols with Video Streaming on the Wireless Mesh Network - Masruroh, Siti Ummi; Fajar, Ahmad Nurul; Alghifari, Mufid Fajar; Wardhani, Luh Kesuma (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Video Streaming is a method to deliver multimedia content that allow files to be used or watched directly without the need to download and save it. Video streaming also include image processing, in image processing there is a component to compare the value of an image, that is PSNR. This research will compare the reactive and proactive routing protocol performance of AOMDV and DSDV using PSNR, Packetloss, and Throughput parameters in Wireless Mesh Network (WMN) for video streaming. The simulation uses 4, 16, 36, 64, and 100 nodes. The results of this research is AOMDV routing protocol with the greater variation in the number of nodes and the distance between nodes resulting in higher packet loss, decreasing throughput and decreasing values of PSNR. While in DSDV routing protocol with the greater variation in the number of nodes and distance between nodes has an impact on the increase of packetloss value, a very drastic decrease throughput value compared with the AOMDV routing protocol, a decrease in PSNR value and in some scenarios does not produce PSNR values. The comparison of PSNR values between the two routing protocols are also influenced by variations in the number of nodes and distances between nodes along with packetloss and throughput parameters. The greater packetloss will decrease the PSNR value generated.